A relational lens to understand housing affordability in the 21st Century - Upuli Perera; Peter Lee (Journal of Urban Management, 2021)
Housing affordability in the 21st-century requires a new way of understanding the concept. The concept is currently framed around household spending on housing costs. In the 21stcentury, households' aspirations and housing outcomes of local residential environments are increasingly influenced by external labour and capital drivers at a range of scales (regional, national, global). Under such context, this paper suggests the concept of housing affordability should be advanced to understood with a relational view of the world. The relational view, underpinned by Giddens's Theory of Structuration, has the scope to capture how households' housing costs, linked to aspirations and housing outcomes across scales, making this more relevant to the 21stcentury. Empirical evidence to demonstrate this has been drawn from a large-scale housing development project in the West Midlands of England. Increasing understanding of the concept helps formulate policies and planning practices for improving mechanisms to deliver better housing outcomes in an affordable and sustainable manner.
Keywords: 710; Housing affordability; 21stcentury housing context; Giddens's theory of structuration; New settlements in England